2019
DOI: 10.1007/s12369-019-00544-9
|View full text |Cite
|
Sign up to set email alerts
|

Care Workers’ Readiness for Robotization: Identifying Psychological and Socio-Demographic Determinants

Abstract: Successful implementation of robots in welfare services requires that the staff approves of them as a part of daily work tasks. In this study, we identified psychological and socio-demographic determinants associated with readiness for robotization among professional Finnish care-workers. National survey data were collected from professional care workers (n = 3800) between October and November 2016. Random samples were drawn from the member registers of two Finnish trade unions. The data were analyzed with reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 65 publications
2
17
0
1
Order By: Relevance
“…Drawing the sample from the trade union member registers was rationalized by the fact that a high proportion (90%) of Finnish nurses are unionized. The division between practical nurses (64.9%) and registered (35.1%) nurses in the sample was similar to the division between practical (64.7%) and registered (35.3%) nurses in the Finnish care worker population (Turja et al, 2019).…”
Section: Studysupporting
confidence: 75%
“…Drawing the sample from the trade union member registers was rationalized by the fact that a high proportion (90%) of Finnish nurses are unionized. The division between practical nurses (64.9%) and registered (35.1%) nurses in the sample was similar to the division between practical (64.7%) and registered (35.3%) nurses in the Finnish care worker population (Turja et al, 2019).…”
Section: Studysupporting
confidence: 75%
“…Based on that, it can be argued that climate change behaviours are influenced by the prevailing social norm. Social norms towards change influence an individual's readiness (Nilsson et al , 2019; Turja et al , 2020). Further, the level of transport sectoral readiness to change is shaped by sectoral social norms that have a strong impact on the promotion and adoption of behaviours within any change context (Vakola, 2013).…”
Section: Resultsmentioning
confidence: 99%
“…Robot-use self-efficacy beliefs concern people’s confidence in their own abilities to use robots [ 36 , 37 ] and are a technology-specific form of the concept of perceived self-efficacy [ 38 ]. Recent studies on robot-use self-efficacy beliefs have demonstrated a positive association with general attitudes toward robots [ 35 ] and a readiness for robotization among healthcare workers [ 34 , 39 ]. Self-efficacy beliefs are dynamic and can be altered by the context and change over time as information and experience are gained [ 40 ].…”
Section: Introductionmentioning
confidence: 99%